2013
DOI: 10.4236/ars.2013.22014
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Classification of Lands at TM and Envisat Images of Mongolia

Abstract: The aim of this study is to fuse high resolution optical and microwave images and classify urban land cover types using a refined Mahalanobis distance classifier. For the data fusion, multiplicative method, Brovey transform, intensity-huesaturation method and principal component analysis are used and the results are compared. The refined method uses spatial thresholds defined from local knowledge and the bands defined from multiple sources. The result of the refined Mahalanobis distance method is compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…As more and more algorithms and their improved versions have been used to fuse optical and SAR images, researchers have compared the performance of these methods for improving ground object interpretation. For instance, Battsengel et al compared the performance of intensity-hue-saturation (IHS) transform, Brovey transformation, and principal components analysis (PCA) in urban feature enhancement [4]. The analysis revealed that the images transformed through IHS have better characteristics in spectral and spatial separation of different urban levels.…”
Section: Introductionmentioning
confidence: 99%
“…As more and more algorithms and their improved versions have been used to fuse optical and SAR images, researchers have compared the performance of these methods for improving ground object interpretation. For instance, Battsengel et al compared the performance of intensity-hue-saturation (IHS) transform, Brovey transformation, and principal components analysis (PCA) in urban feature enhancement [4]. The analysis revealed that the images transformed through IHS have better characteristics in spectral and spatial separation of different urban levels.…”
Section: Introductionmentioning
confidence: 99%